DESIGN OF SUBSOIL IMPROVEMENT BELOW HALL FLOORS - Peter Turček; Monika Súlovská (Acta Polytechnica CTU Proceedings, 2017)
The construction of an industrial park is now being prepared near the town of Nitra. The investor fixed very strict conditions for the bearing capacity and, above all, the settlement of halls and their floors. The geological conditions at the construction site are difficult: there are soft clay soils with high compressibility and low bearing capacity. A detailed analysis of soil improvement was made. Stone columns were prepared to be fitted into an approximately 5 m thick layer of soft clay. The paper shows the main steps used in the design of the stone columns.